Online tendering : cost effective and time saving alternative towards fair tendering - Alam, Mahabub; Sayed, Abu; Chowdhury, Sadat Mursalin (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.